Non-Vascularized Fibular Bone Graft for Giant Cell Tumor of the Distal Ulna: A Case Report - Albertus D. Noersasongko; Haryanto Sunaryo; Tommy Suharso; Andriessanto Lengkong; Rangga Rawung; Stefan Kambey; Patrick S. Arikalang (Medical Scope Journal, 2024)
Abstract: Cases of bone giant cell tumors (GCT) are rarely found, generally benign and locally aggressive tumors. Surgical resection is the universal standard for treatment of bone GCT. Non vascularized fibular graft (NVFG) is useful in the reconstruction of skeletal defects, especially in cases of scarred and avascular recipient sites and patient with tumor surrounded by poor tissue condition. We report a 53-year-old woman, with a lump in her left hand for three years. X-ray examination revealed a mass with firm border and regular edge that reached the epiphysis expansively with thinning of the cortex in the distal region of the left ulna. Tumor excision was performed with open reduction internal fixation (ORIF) and fibular bone graft. To date, GCT is one of the most obscure and intensively examined bone tumors, and its histological images do not predict the clinical outcome. Moreover, many unanswered questions regard to the treatment and prognosis without any consensus regarding the ideal treatment selection. NVFG osteosynthesis shows encouraging results, and adequate therapy, wound care and patient compliance affect the patient’s outcome. In conclusion, NVFG and internal fixation are effective options for post tumor excision, and osteosynthesis has encouraging result. Keywords: non vascularized fibular graft (NVFG); giant cell tumor; bone graft; ulna